COMPARATIVE EFFICACY OF AMIODARONE AND BISOPROLOL IN TREATMENT OF VENTRICULAR PREMATURE BEATS IN PATIENTS WITH METABOLIC SYNDROME - V. M. Provotorov; M. L. Gluhovsky (Рациональная фармакотерапия в кардиологии)
Aim. Comparative study of amiodarone and bisoprolol efficacy in patients with ventricular arrhythmia and metabolic syndrome.Methods. 146 patients with the AHA/NHLBI 2005 metabolic syndrome and symptomatic ventricular arrhythmia were included in the study. 52 patients received regular oral amiodarone (200 mg daily, 5 days a week) therapy, 55 patients received bisoprolol (10 mg daily) treatment and 39 patients did not receive any antiarrhythmic therapy (control group). Treatment efficacy was evaluated by Holter monitoring (before start and after 1, 3, 6, 9, 12 months of therapy).Results. Significant efficacy advantage of bisoprolol vs this of amiodarone was observed in 12 months of therapy (50.0% of effectively treated patients vs 17.3%, p=0.02). Significant difference in a number of patients ceased therapy because of antiarrhythmic effect loss was also revealed (20.0% vs 46.1%, p=0.004). A number of patients stopped therapy because of side effects was comparable in the both groups. Patient age younger than 42 years old in combination with a number of ventricular premature beats morphology less than 4 allowed predicting effective antiarrhythmic treatment for both drugs with sensitivity of 70.3% and specificity of 65.0%.Conclusion. Bisoprolol have an advantage (versus amiodarone) within 9-12 month therapy in patients with ventricular premature beats and metabolic syndrome. Drug refractoriness and side effects monitoring is necessary.